A case series on the basic concept and design of removable partial dentures: support and bracing considerations - Jun Takebe (BMC Oral Health)
Abstract Background When designing removable partial dentures, maximizing the effectiveness of support and bracing is necessary to minimize denture movement. Therefore, it is essential to emphasize the importance of providing patients with appropriate, safe, and secure removable partial dentures and have clinicians rerecognize the concept and importance of support and bracing. This study aimed to present extension-base removable partial dentures through six specific clinical case series and describe the effect of support and bracing action on denture design, which is essential for denture movement minimization. A Case Series Study Case presentation: The case series highlights the importance of utilizing the contact between the axial surface of the abutment tooth and denture components to provide effective support and bracing action. Furthermore, it emphasizes the need to improve the bracing action by connecting the minor connector and proximal plate with the guiding plane set for multiple teeth (frictional control), control the direction of the denture during the placement/removal (path of insertion), and consider the major connector form to improve the support and bracing actions. Effective support and bracing actions are necessary not only for the retainer but also for the denture components, including the design of the denture base and major connector. Removable partial dentures with “frictional control” and “path of insertion” are expected to reduce denture movement and improve stability. Conclusions The denture design described in this study is essential in pre- and postgraduate dental education, and the author believes that it will be helpful for dental students, interns, or residents in clinical practice.